Services Enabler Architecture for Smart Grid and Smart Living Services Providers under Industry 4.0 - Batista, Nelson (2018)
For an industry 4.0 environment, the management and offering of services, falls over the construction of a stable and reliable sensor and actuator infrastructure. Industry 4.0 is undergoing increase advancement, infrastructure availability and public acceptance, mainly boosted by the Interconnected Things. The public acceptance drives an increase on investments, carrying an insurgence of companies competing with each other to gain market. Although lessening costs, this insurgence has brought heterogeneous infrastructures and solutions availability, challenging services providers. Among the challenges the security and different technology solutions support are of the most importance. The scattering of solutions and software code have to be conveniently gathered to avoid weak-points, eventually, a menace to be explored by hackers. This paper is a contribution in order to embraces those challenges in a new architecture framework able of supporting the creation of solutions for Smart Grid and Smart Living services providers under the industry 4.0 paradigm. The architecture framework design offers security, simplicity of implementation and maintenance, and is resilient to failures or attacks and technologically independent. Field tests are reported in order to evaluate key aspects of the proposed architecture.